An ethical code of conduct for the non-proliferation of biological agents among Malaysian businesses - Abdul Majid, Marina (2015)
Currently, export control monitoring of the proliferation of biological agents in Malaysia falls within the ambit of the Strategic Trade Act 2010 (STA 2010), a law drafted by Malaysia's Ministry of International Trade and Industry (MITI). At the same time, businesses in Malaysia have not gone so far as to initiate an ethical code of conduct to prevent biological agents from being proliferated for bioterrorism. Beneficence provides the ethical foundation for these relevant businesses to prevent bioterrorism. For that reason, this study has the objective of exploring best practices that can be turned into an ethical code of conduct for commercial culture collection businesses in Malaysia, guiding them to prevent biological agents from being proliferated for bioterrorism. The methodology for this study is qualitative based on primary sources such as legislations and international organizational documents as well as secondary sources - all of which are collated and examined through a content analysis. The results of this study indicate lessons learned from the nuclear industry that ought to be incorporated in the envisioned ethical code of conduct such as sharing illicit request information of biological agents among all parties, detection methods, reasons for refusal, personal particulars of requesters, and conducting transactions among peers that adhere to the non-proliferation of biological agents. The Business Ethic Institute of Malaysia (BEIM) and MITI can introduce, create awareness of, and draft a model ethical code of conduct for the non-proliferation of biological agents to guide commercial culture collection businesses in Malaysia.